Optimasi Formula Mikroenkapsulasi Ekstrak Rimpang Temulawak (Curcuma xanthorrhiza Roxb.) dengan Penyalut Berbasis Air - Nugraheni, Ade; Yunarto, Nanang; Sulistyaningrum, Novi (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2015)
Java turmeric (Curcuma xanthorrhiza Roxb.) is a native plant of Indonesia which has been proved as anti-inflamation, antioxidant, antimicrobial, antitumor, hepatoprotective and antihyperlipidemic agent. The bitter taste with pungent aroma of java turmeric, improper storage that decreasing essential oil and curcuminoid level can be prevented by coating java turmeric as microcapsule. Recently, many microcapsule formulation is made based on organic solvent which have high risk on toxicity and also flammable. The study aimed to produce microcapsule using water based coating material from mixture of tapioca starch and carboxymethylceIlulose (CMC). There are 3 formulas of coating material that were used in this study, with proportion (w/v) of tapioca starch and CMC in formula I (3% : 1 %), formula II (2% : 2 %), and formula III (1% : 3%). The results showed that microcapsule with coating material made from formula III was the best, regarding to the measurements of physical parameter (recovery, water content, absorption efficiency, flow rate and particle size) and chemical parameter (curcumin content) compared to formula I and II. The higher CMC concentration on coating material compotition, the better microcapsule will be produced.